The pilot's handbook of aeronautical knowledge - Illman, Paul E.; Gailey, Gene E. (New York : McGraw-Hill, 2013)
"The bestselling source of complete pilot information is now completely revised and updated"-Provided by publisher.
Earning your wings : rewards and responsibilities -- Principles of flight -- Airplanes and engines -- Flight instruments -- Airplane performance -- Weather -- Navigation -- The airspace system -- Airports -- Radio communications -- VFR flight planning -- Emergency procedures -- Wake turbulence -- Medical facts for pilots.
Keywords: Airplanes -- Piloting -- Handbooks, manuals, etc; Aeronautics -- Handbooks, manuals, etc